2016
DOI: 10.1055/s-0042-119211
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α is Inversely Related to Free Thyroxine in Euthyroid Subjects Without Diabetes

Abstract: Lower thyroid functional status within the euthyroid range may confer increased atherosclerosis susceptibility, as evidenced by increased intima media thickness and coronary artery calcification. Associations of lower thyroid functional status with pro-atherogenic (inflammatory) biomarkers may also extend into the euthyroid range. Here we established relationships of plasma tumor necrosis factor-α (TNF-α) with thyroid stimulating hormone (TSH) and free thyroxine (free T) in euthyroid subjects with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…12,13 Moreover, increased levels of oxidized LDL have been demonstrated in euthyroid subjects with high normal TSH levels. 14 Taken together, these data 14,[45][46][47] make it unlikely that a higher PON-1 activity in relation to low-normal thyroid function is explained by thyroid hormone-mediated effects on IL-1 and TNF-a or on (systemic) oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 Moreover, increased levels of oxidized LDL have been demonstrated in euthyroid subjects with high normal TSH levels. 14 Taken together, these data 14,[45][46][47] make it unlikely that a higher PON-1 activity in relation to low-normal thyroid function is explained by thyroid hormone-mediated effects on IL-1 and TNF-a or on (systemic) oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…45 Hypothyroidism may increase IL-1 and TNF-a, 46 whereas higher levels of TNF-a are also found in subjects with low-normal thyroid function. 47 In addition, oxidized lipids are recognized to inhibit PON-1 activity. 12,48,49 In this context, it is relevant that low-density lipoprotein (LDL) oxidation in vitro is exaggerated in both hypothyroidism and hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The underlying mechanisms of relationships between sensitivity indices to THs and MAFLD stay entirely unknown, but may contain chronic inflammation, dysregulation of mitochondrial homeostasis, endoplasmic reticulum stress and decreased insulin sensitivity. [34][35][36][37][38] Chronic inflammation was considered to be one of the key pathogenesis of MAFLD and could promote the incidence of MAFLD. 35 Studies revealed that low FT4 was related to higher levels of inflammatory biomarkers (eg, tumor necrosis factor alpha (TNF-α), interleukin (IL)-1, IL-6 and interferon-γ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the detected upregulation of the lipopolysaccharide binding protein (LBP), an acute-phase protein, and the corresponding receptor indicated an involvement in immunological responses. The complex and bidirectional relationship between THs and processes of the immune response is subject of an ongoing discussion [58][59][60]. LBP binds to lipopolysaccharides of bacteria and interacts with the CD14 receptor that triggers an immune response, leading to M1activation of macrophages and consequently an increased production of proinflammatory cytokines like tumor necrosis factor alpha (TNFα).…”
Section: Molecular Effects Of Thyroid Hormone Administrationmentioning
confidence: 99%